La escritura argumentada como estrategia para el fortalecimiento de la enseñanza-aprendizaje en la asignatura de Lengua y Literatura. - Pastuña Suntasig, José Moisés (2022)
The argumentative writing as a strategy for the strengthening of teaching-learning in the subject of Language and Literature, arises from the need to strengthen the teaching didactics, due to the difficulties encountered in the development of the skills of the argumentative writing, before it is raises the following objective "Strengthen the teaching-learning process of the subject of Language and Literature in sixth grade students of the Leonardo Moscoso Moreno School of Basic Education through argumentative writing." The research methodology was directed with the critical paradigm and the qualitative approach, the scope of the research was exploratory and descriptive, the assumed theoretical method was inductive, two techniques were used: observation and interview, the sample of 20 students and 1 teacher-director, was under the non-probabilistic method. The main results obtained reflected the deficiencies in relation to the argued writing in the students, due to the lack of use of this strategy in the teaching-learning process, for which, eight argued writing workshops were proposed, based on the theoretical contributions. de Gallego and Rodríguez, promoting through argumentative writing the macro skills of the area of Language and Literature.